DEHYDRATION MELTING AND THE GRANULITE TRANSITION IN METAPELITES FROM SOUTHERN NAMAQUALAND, SOUTH-AFRICA - Waters, D; Whales, C (Springer-Verlag, 1984)
In a prograde amphibolite-granulite transition zone in the Namaqualand Metamorphic Complex, metapelites show an interbanding of the amphibolite facies association biotite+sillimanite+quartz with the granulite facies association garnet+cordierite+K-feldspar. Relict graded bedding shows that compositional banding is of sedimentary origin. The garnet-cordierite-K-feldspar gneisses contain quartzofeldspathic segregations surrounding garnets, and have more Fe-rich bulk compositions than the biotite-sillimanite schists. The contrasting asemblages could have formed at the same pressure and temperature provided that a(H2O) was systematically lower in the garnet-cordierite-K-feldspar layers. The a(H2O) reduction resulted from the production of silicate melt by a vapour-absent continuous Fe-Mg reaction such as biotite+sillimanite+quartz=garnet+K-feldspar+liquid which affects Fe-rich compositions before vapour-absent melting occurs in more Mg-rich rocks. The segregations represent the solid and liquid products of the reaction. Such processes imply local control of a(H2O), and indicate that this granulite transition did not result from a regional influx of metasomatising fluids. © 1984 Springer-Verlag.